Estabilização de areia com cinza volante e cal; efeito do cimento como aditivo e de brita na mistura - Nardi, José Vidal (1975)
Study on the stabilization of sand with fly ash and hidrated calcitic lime, and the effects of admixing portland cement and crushed stone on the compressive strength of the mix. In order to enhance fly ash role the soil chosen was a non-cohesive one - a uniform dune sand - which is not quite suitable for stabilization with cement and not at all with lime. Stabilization effect results from cementation of sand grains by the product from pozzolanic reaction of lime with fly ash in wet condition. Three different mixtures were studied. First mixture: lime 4%, fly ash 13%, sand 83%, considered the basic one. Second mixture: same with 1% portland cement of high early strength to study its effect as additive. Third mixture: lime 4%, fly ash 13%, sand 53%, crushed stone 30%, added 1% portland cement of high early strenght; studied effect of adding crushed stone to the mix. All mixes were compacted using two energies: intermediate and modified compactive efforts. Cylindrical specimens, height 20 cm, diameter 10 cm. Curing ages: 7, 14 and 28 days. Texting: axial compression and diammetrical (split tensile) compression. Unconfined compressive strengths varied from 2,1 to 94 kgf/cm2 and tensile strength from 2,2 to 10,4 kgf/cm2, depending on mix composition, compaction effort and curing time. Laboratory experiments confirm possibilities of this king of soil stabilization suitable for many applications in sub-base and base pavement courses.